Helicobacter cyclurae sp. Nov., Isolated From Endangered Blue Iguanas (Cyclura lewisi) - Chan, Nathan; Shen, Zeli; Mannion, Anthony; Kurnick, Susanna; Popescu, Ioana S.; Burton, Frederic J.; Calle, Paul P.; Fox, James G. (Frontiers in Ecology and Evolution, 2021)
Blue iguanas (Cyclura lewisi) are endangered reptiles found only on Grand Cayman. Previously, DNA for a novel Helicobacter species GCBI1 was detected in sick and dead iguanas. In the current study, fecal and cloacal swab samples were obtained from 25 iguanas. Using molecular and microbiological techniques, a novel Helicobacter species was cultured from feces and characterized, which we propose the name Helicobacter cyclurae. This novel helicobacter had a prevalence of 56% by PCR and 20% by culture in samples analyzed. The type strain MIT 16-1353 was catalase, oxidase, and gamma-glutamyl transpeptidase positive. By electron microscopy, H. cyclurae has a curved rod morphology and a single sheathed polar flagellum. Phylogenetic analysis using 16S rRNA, gyrB and hsp60 indicated these strains were most closely related to Helicobacter sp. 12502256-12 previously isolated from lizards. H. cyclurae has a 1.91 Mb genome with a GC content of 33.37%. There were 1,969 genes with 4 notable virulence genes, high temperature requirement-A protein-secreted serine protease, gamma-glutamyl transpeptidase, fibronectin/fibrinogen binding protein, and neutrophil-activating protein. Whole-genome phylogenetic, average nucleotide identity, and digital DNA-DNA hybridization analysis confirmed H. cyclurae is a novel species, and the first helicobacter cultured and characterized from blue iguanas.